Captivate - Jones, Carrie, 1971- (Jones, Carrie. Need series, 2010)
High school junior Zara and her friends continue to try to contain the pixies that threaten their small Maine town, but when a Valkyrie takes Zara's boyfriend, Nick, to Valhalla, the only way to save him is to trust a pixie king, Astley.